Nanolignin as Nucleating Agents Promoting Crystallization of Isotactic Polypropylene. (23rd March 2023) - Chen, Jing; Yang, Tao; Zhu, Yongchen; Luo, Zhenyang; Ma, Xiaofeng
Abstract : Lignin is the second most abundant pollution-free biomass material. However, most of lignin is discarded as waste in river or burned as fuel, which results in serious environmental pollution problems and low utilization efficiency of lignin at present. Thus, high-value utilization of lignin has become a hot research field. Herein, nanolignin (nano-Lig) is prepared successfully by the self-assembly method, and then nano-Lig and isotactic polypropylene (iPP) are mixed to prepare a series of nano-Lig/iPP composites by the solution blending method. Nano-Lig not only enhance thermostability of iPP but also improve crystallization properties of iPP. When 1.0 wt% nano-Lig was added in iPP, the crystallinity of iPP increased by 6.39% compared to iPP. Nano-Lig can increase the crystallization rate of iPP through investigation of kinetics of nonisothermal crystallization, suggesting nano-Lig can be used as a nucleating agent for iPP.